Nickel-cobalt-aluminum composite hydroxide
A nickel-cobalt-aluminum composite hydroxide with controlled crystallization and washing processes effectively reduces impurities, enhancing lithium-ion battery capacity and safety by ensuring efficient lithium diffusion and improved cycle characteristics.
Patent Information
- Application Number
- JP2022087160
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-05-27
- Publication Date
- 2025-01-22
- Estimated Expiration
- 2037-12-08
AI Technical Summary
Existing lithium nickel cobalt composite oxides used as positive electrode active materials in secondary batteries contain impurities such as sulfate, chlorine, and sodium, which inhibit lithium diffusion, reduce battery capacity, and pose safety risks due to irreversible capacity and excess lithium accumulation in the negative electrode.
A nickel-cobalt-aluminum composite hydroxide is developed with controlled crystallization and washing processes using an ammonium bicarbonate solution to reduce impurities like sodium, chlorine, and sulfate to less than 0.0005% by mass, achieving a specific surface area of 30 to 50 m²/g and a narrow particle size distribution.
The composite hydroxide precursor enhances lithium-ion battery capacity and safety by minimizing impurities, ensuring efficient lithium diffusion and improved cycle characteristics.
Smart Images

Figure 0007619978000003 
Figure 0007619978000004 
Figure 0007619978000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a nickel-cobalt-aluminum composite hydroxide, which is a precursor of a positive electrode active material and is composed of secondary particles formed by agglomeration of primary particles containing nickel, cobalt, and aluminum, or primary particles and secondary particles. To things Regarding. [Background technology]
[0002] In recent years, with the widespread use of portable electronic devices such as smartphones, tablet terminals, and notebook computers, there is an increasing need for the development of high-power secondary batteries, including small, lightweight nonaqueous electrolyte secondary batteries having high energy density, as well as batteries for hybrid and electric vehicles.
[0003] Lithium ion secondary batteries are an example of secondary batteries that can meet such needs. Lithium ion secondary batteries are composed of a positive electrode, a negative electrode, and an electrolyte, and the active materials of the positive electrode and the negative electrode are made of materials that can extract and insert lithium. Lithium ion secondary batteries are still being actively researched and developed, and among them, lithium ion secondary batteries that use layered or spinel type lithium metal composite oxides as the positive electrode active material can obtain a high voltage of 4V, and are therefore being put into practical use as batteries with high energy density.
[0004] Among these, lithium nickel cobalt composite oxide has attracted attention as a material that has good cycle characteristics of battery capacity and can obtain high output with low resistance, and in recent years, it is also suitable as a power source for electric vehicles and hybrid vehicles that are restricted in mounting space, and is considered important as an on-board power source. Generally, lithium nickel cobalt composite oxide is produced by mixing a nickel cobalt composite hydroxide, which is a precursor, with a lithium compound and baking the mixture.
[0005] This nickel-cobalt composite hydroxide contains impurities such as sulfate radicals, chlorine radicals, and sodium derived from the raw materials and chemicals used in the manufacturing process. These impurities induce side reactions and the like in the process of mixing the nickel-cobalt composite hydroxide with a lithium compound and firing it, thereby worsening the reaction with lithium and reducing the crystallinity of the lithium-nickel-cobalt composite oxide, which has a layered structure.
[0006] When a lithium nickel cobalt composite oxide with low crystallinity is used as a positive electrode active material in a battery, the lithium diffusion in the solid phase is hindered, resulting in a decrease in battery capacity. In addition, since these impurities hardly contribute to the charge / discharge reaction, the battery must use an extra negative electrode material to cover the irreversible capacity of the positive electrode material. As a result, the capacity of the battery as a whole is reduced per weight or volume, and excess lithium accumulates in the negative electrode as irreversible capacity, which is a safety issue.
[0007] Impurities include sulfate radicals, chlorine radicals, sodium, etc., and techniques for removing these impurities have been disclosed.
[0008] For example, Patent Document 1 discloses a method in which a crystallization step is performed to obtain a niobium-containing transition metal composite hydroxide, and the obtained niobium-containing transition metal composite hydroxide is washed with an aqueous solution of a carbonate such as potassium carbonate, sodium carbonate, or ammonium carbonate, thereby reducing sulfate radicals and chlorine radicals.
[0009] Furthermore, Patent Document 2 discloses that in a process for producing a nickel manganese cobalt composite hydroxide through a crystallization reaction, the alkaline solution used for adjusting the pH is a mixed solution of an alkali metal hydroxide and a carbonate, thereby reducing the impurities of sulfate radicals, chlorine radicals, and carbonate radicals.
[0010] Furthermore, Patent Documents 3 and 4 disclose that nickel-manganese composite hydroxide particles or nickel composite hydroxide particles having a void structure inside the particles obtained in a crystallization step are washed with an aqueous solution of a carbonate such as potassium carbonate, sodium carbonate, potassium hydrogen carbonate, or sodium hydrogen carbonate, thereby reducing the sulfate radicals, chlorine radicals, and sodium.
[0011] Patent Document 5 discloses that a nickel-cobalt-M element-containing aqueous solution or aqueous dispersion obtained by mixing a nickel ammine complex, a cobalt ammine complex, and an M element source is heated to thermally decompose the nickel ammine complex and the cobalt ammine complex, thereby using a nickel-cobalt-M element-containing composite compound having a low content of impurities such as sulfate radicals, chlorine radicals, sodium, and iron. [Prior art documents] [Patent documents]
[0012] [Patent Document 1] JP 2015-122269 A [Patent Document 2] JP 2016-117625 A [Patent Document 3] International Publication No. 2015 / 146598 [Patent Document 4] JP 2015-191848 A [Patent Document 5] International Publication No. 2012 / 020768 Summary of the Invention [Problem to be solved by the invention]
[0013] However, Patent Documents 1 and 2 do not mention the removal of sodium at all. In Patent Documents 3 and 4, even in a solid precursor with a porosity of about 3%, sodium still remains at 0.001 to 0.015 mass%, and sodium reduction is insufficient. Furthermore, in Patent Document 5, since a nickel-cobalt-M element-containing composite compound is obtained by thermal decomposition, it is questionable whether sufficient battery characteristics will be obtained when it is used as a positive electrode active material from the viewpoints of particle sphericity, particle size distribution, and specific surface area. In particular, the focus is not on nickel-cobalt-aluminum composite hydroxide containing aluminum.
[0014] Therefore, the object of the present invention is to reliably reduce the content of impurities, particularly sodium, which hardly contributes to charge / discharge reactions, and to produce a nickel-cobalt-aluminum composite hydroxide containing nickel, cobalt, and aluminum, which is a precursor of a positive electrode active material for a lithium ion secondary battery that can achieve a high capacity. Things The purpose is to provide. [Means for solving the problem]
[0015] A nickel-cobalt aluminum composite hydroxide according to one embodiment of the present invention is a nickel-cobalt aluminum composite hydroxide that is a precursor of a positive electrode active material and is composed of secondary particles in which primary particles containing nickel, cobalt, and aluminum are aggregated, or the primary particles and the secondary particles, and the nickel-cobalt aluminum composite hydroxide has a sodium content of less than 0.0005% by mass. The chlorine content is 0.01% by mass or less. It is characterized by the above.
[0016] In this way, sodium and chlorine root It is possible to provide a nickel-cobalt-aluminum composite hydroxide containing nickel, cobalt, and aluminum, which is a precursor of a positive electrode active material for a lithium ion secondary battery that can reliably reduce the content of nickel, cobalt, and aluminum and can achieve a high capacity.
[0017] In one embodiment of the present invention, the specific surface area of the nickel-cobalt-aluminum composite hydroxide is 30 to 50 m 2 / g may also be used.
[0018] In this way, it is possible to provide a nickel-cobalt-aluminum composite hydroxide, which is a precursor of a positive electrode active material that can be used to obtain a lithium ion secondary battery with a higher capacity by increasing the specific surface area.
[0019] In one embodiment of the present invention, the content of sulfate radicals contained in the nickel-cobalt-aluminum composite hydroxide is 0.2 mass% or more. Below and You may do so.
[0020] In this way, sulfuric acid Root It is possible to provide a nickel-cobalt-aluminum composite hydroxide, which is a precursor of a positive electrode active material that can reliably reduce the content and obtain a lithium-ion secondary battery with a higher capacity.
[0021] In this case, in one embodiment of the present invention, an index showing the spread of the particle size distribution of the nickel-cobalt-aluminum composite hydroxide, [(d90-d10) / average particle size], may be 0.55 or less.
[0022] In this way, the proportion of fine particles and large particles is reduced when the positive electrode active material is used, and therefore a lithium ion secondary battery using this positive electrode active material in the positive electrode is safe and can obtain good cycle characteristics and battery output.
[0023] In one embodiment of the present invention, the nickel-cobalt-aluminum composite hydroxide is represented by the general formula: 1-x-y Co x Al y (OH) 2+a (However, it may be expressed as 0.05≦x≦0.35, 0.01≦y≦0.20, x+y<0.40, and 0≦a≦0.5).
[0024] In this manner, the sodium content of the nickel-cobalt-aluminum composite hydroxide can be reliably reduced, and a nickel-cobalt-aluminum composite hydroxide can be provided, which is a precursor of a positive electrode active material that can provide a lithium-ion secondary battery with a high capacity. Effect of the Invention
[0029] According to the present invention, a nickel-cobalt-aluminum composite hydroxide containing nickel, cobalt, and aluminum is prepared, which is a precursor of a positive electrode active material for a lithium ion secondary battery that can reliably reduce the content of sodium and increase the capacity. Things can be provided. [Brief description of the drawings]
[0030] [Figure 1] FIG. 1 is a cross-sectional SEM photograph of a nickel-cobalt-aluminum composite hydroxide according to one embodiment of the present invention, showing that the internal structure is a solid structure. [Diagram 2] FIG. 2 is a process diagram showing an outline of a method for producing a nickel-cobalt-aluminum composite hydroxide according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0031] The present inventors have conducted extensive research to solve the above problems, and have found that, in particular in the production of nickel-cobalt-aluminum composite hydroxide containing aluminum, the reaction atmosphere in the crystallization step can be controlled, the alkali solution used in the crystallization step is a mixed solution of an alkali metal hydroxide and a carbonate, and the transition metal composite hydroxide obtained in the crystallization step is washed with an ammonium hydrogen carbonate solution, which is a washing solution containing hydrogen carbonate (bicarbonate), in the washing step, thereby making it possible to more efficiently reduce the impurities, sulfate radicals, chlorine radicals and sodium, and have completed the present invention. Preferred embodiments of the present invention will now be described.
[0032] The present embodiment described below does not unduly limit the contents of the present invention described in the claims, and can be modified within the scope of the present invention. Furthermore, not all of the configurations described in the present embodiment are necessarily essential as a means for solving the problems of the present invention. The nickel-cobalt-aluminum composite hydroxide, the method for producing the nickel-cobalt-aluminum composite hydroxide, and the lithium-nickel-cobalt-aluminum composite oxide according to one embodiment of the present invention will be described in the following order. 1. Nickel-cobalt-aluminum composite hydroxide 2. Lithium nickel cobalt aluminum composite oxide 3. Manufacturing method of nickel-cobalt-aluminum composite hydroxide 3-1.Crystallization process 3-1-1. Nucleation process 3-1-2. Particle growth process 3-2. Cleaning process
[0033] <1. Nickel-cobalt-aluminum composite hydroxide> A nickel-cobalt-aluminum composite hydroxide according to one embodiment of the present invention is a precursor of a positive electrode active material, which is composed of secondary particles in which primary particles containing nickel, cobalt, and aluminum are aggregated, or the primary particles and the secondary particles.
[0034] The nickel-cobalt-aluminum composite hydroxide is characterized in that the sodium content in the nickel-cobalt-aluminum composite hydroxide is less than 0.0005% by mass. BEST MODE FOR CARRYING OUT THE DISCLOSURE Hereinafter, the nickel-cobalt-aluminum composite hydroxide according to one embodiment of the present invention will be specifically described.
[0035] [Particle composition] Nickel-cobalt-aluminum composite hydroxide has the following composition: 1-x-y Co x Al y (OH) 2+a (However, it is preferable that the ratio is adjusted so as to satisfy the following conditions: 0.05≦x≦0.35, 0.01≦y≦0.20, x+y<0.40, 0≦a≦0.5).
[0036] In the above general formula, x, which indicates the cobalt content, is preferably 0.05≦x≦0.35. By adding an appropriate amount of cobalt, it is possible to improve cycle characteristics and further reduce the expansion and contraction behavior of the crystal lattice due to the desorption and insertion of lithium accompanying charge and discharge. If the cobalt content is too low and x is less than 0.05, it is difficult to obtain the expected effect, which is not preferable. On the other hand, if the cobalt content is too high and x exceeds 0.35, the initial discharge capacity may decrease significantly, and further, there is a problem that is disadvantageous in terms of cost, which is not preferable. Therefore, x, which indicates the cobalt content, is preferably 0.05≦x≦0.35, and considering the battery characteristics and cost more, 0.07≦x≦0.25 is preferable, and in practice, it is more preferable to set it to 0.10≦x≦0.20.
[0037] In addition, y, which indicates the aluminum content, is preferably 0.01≦y≦0.2. When aluminum is added within this range, durability and safety can be further improved when the battery is used as a positive electrode active material. In particular, if aluminum is adjusted so as to be uniformly distributed inside the particle, the above effect can be obtained throughout the particle, so that the same amount of aluminum added can exert a greater effect and the capacity decrease can be suppressed. If the amount of aluminum added is too small and y is less than 0.01, it is difficult to obtain the expected effect, which is not preferable. On the other hand, if it exceeds 0.2, the amount of aluminum added is too large, and the metal elements contributing to the Redox reaction are reduced, which is not preferable because the battery capacity may decrease.
[0038] The method for analyzing the composition of the particles is not particularly limited, but for example, the composition can be determined by a chemical analysis method such as acid decomposition-ICP emission spectrometry.
[0039] [Particle structure] The nickel-cobalt-aluminum composite hydroxide is composed of spherical secondary particles formed by agglomeration of a plurality of primary particles. The primary particles constituting the secondary particles may have various shapes such as plate-like, needle-like, rectangular, elliptical, and rhombohedral. In addition, the present invention can be applied to the case where the agglomeration state of a plurality of primary particles is not only agglomerated in random directions, but also agglomerated in the long diameter direction of the particles radially from the center.
[0040] The agglomerated state is preferably such that plate-like or needle-like primary particles are agglomerated in random directions to form secondary particles, because in the case of such a structure, almost uniform voids are generated between the primary particles, and when mixed with a lithium compound and fired, the molten lithium compound spreads throughout the secondary particles, allowing sufficient diffusion of lithium.
[0041] The method for observing the shapes of the primary particles and the secondary particles is not particularly limited, but the shapes can be measured by observing a cross section of the nickel-cobalt-aluminum composite hydroxide using a scanning electron microscope (SEM) or the like.
[0042] [Particle internal structure] The nickel-cobalt-aluminum composite hydroxide according to one embodiment of the present invention has a solid structure and does not have a hollow structure or a porous structure inside the secondary particles. Since there are no voids inside the secondary particles, the particle strength is the best. Therefore, the life of the positive electrode active material is extended.
[0043] This solid structure can be confirmed by observing the cross section of the nickel-cobalt-aluminum composite hydroxide particles with a scanning electron microscope (SEM).
[0044] [Average particle size (MV)] The nickel-cobalt-aluminum composite hydroxide is preferably adjusted to have an average particle size of 3 to 20 μm. If the average particle size is less than 3 μm, the packing density of the particles may decrease when the positive electrode is formed, which is not preferable because the battery capacity per volume of the positive electrode may decrease. On the other hand, if the average particle size exceeds 20 μm, the specific surface area of the positive electrode active material decreases, and the interface with the electrolyte of the battery may decrease, which is not preferable because the resistance of the positive electrode may increase and the output characteristics of the battery may decrease. Therefore, if the average particle size of the nickel-cobalt-aluminum composite hydroxide is adjusted to 3 to 20 μm, preferably 3 to 15 μm, and more preferably 4 to 12 μm, the lithium ion secondary battery using this positive electrode active material as the positive electrode material can have a large battery capacity per volume, high safety, and good cycle characteristics.
[0045] The method for measuring the average particle size is not particularly limited, but for example, it can be determined from a volume-based distribution measured using a laser diffraction / scattering method.
[0046] [Impurity content] In general, nickel-cobalt composite hydroxide and nickel-cobalt aluminum composite hydroxide contain sulfate radicals, chlorine radicals, and sodium as impurities. These impurities cause the reaction with lithium to deteriorate and hardly contribute to the charge-discharge reaction, so it is preferable to remove them as much as possible and reduce their content. In addition, although details will be described later, when producing nickel-cobalt aluminum composite hydroxide containing aluminum, it is preferable to use sodium aluminate and sodium hydroxide rather than sulfate, and the sodium concentration during crystallization is higher than when producing nickel-cobalt composite hydroxide not containing aluminum, making it difficult to remove sodium by washing. Conventionally, techniques for removing these impurities have been disclosed, but they are still insufficient.
[0047] Therefore, the nickel-cobalt-aluminum composite hydroxide according to one embodiment of the present invention is characterized in that the sodium content contained therein is less than 0.0005% by mass. In this way, it is possible to provide a nickel-cobalt-aluminum composite hydroxide containing nickel, cobalt, and aluminum, which is a precursor of a positive electrode active material for a lithium-ion secondary battery that can reliably reduce the sodium content and increase the capacity.
[0048] The nickel-cobalt-aluminum composite hydroxide preferably has a sulfate radical content of 0.2 mass % or less and a chlorine radical content of 0.01 mass % or less. In this way, it is possible to provide a nickel-cobalt-aluminum composite hydroxide that is a precursor of a positive electrode active material for a lithium ion secondary battery capable of reliably reducing the sulfate radical, chlorine radical, and sodium contents and improving the battery characteristics.
[0049] The content of each impurity can be determined, for example, by the following analytical methods. Sodium can be determined by acid decomposition-atomic absorption spectrometry, acid decomposition-ICP emission spectrometry, etc. Sulfate radicals can be determined by analyzing the total sulfur content of nickel-cobalt-aluminum composite hydroxide by combustion infrared absorption spectrometry, acid decomposition-ICP emission spectrometry, etc., and calculating the total sulfur content as sulfate radicals (SO4 2- The chlorine radicals can be determined by converting the nickel-cobalt-aluminum composite hydroxide directly, or by separating the chlorine radicals contained in the nickel-cobalt-aluminum composite hydroxide through a distillation process in the form of silver chloride or the like, and analyzing the result using X-ray fluorescence (XRF) analysis.
[0050] [Particle size distribution] The nickel-cobalt-aluminum composite hydroxide is preferably adjusted so that the index showing the spread of the particle size distribution of the particles, [(d90-d10) / average particle size], is 0.55 or less.
[0051] If the particle size distribution is wide and the index showing the spread of the particle size distribution, [(d90-d10) / average particle size], exceeds 0.55, there will likely be a large number of fine particles whose particle size is very small compared to the average particle size, and a large number of particles whose particle size is very large compared to the average particle size (large diameter particles).
[0052] Such particle size distribution characteristics at the precursor stage also have a large effect on the positive electrode active material obtained after the firing process. When a positive electrode is formed using a positive electrode active material containing a large amount of fine particles, not only may the local reaction of the fine particles cause heat generation, which may reduce safety, but also may cause the fine particles with a large specific surface area to selectively deteriorate, which may deteriorate the cycle characteristics, which is not preferable. On the other hand, when a positive electrode is formed using a positive electrode active material containing a large amount of large particles, the reaction area between the electrolyte and the positive electrode active material may not be sufficient, which may reduce the battery output due to an increase in reaction resistance, which is not preferable.
[0053] Therefore, in the particle size distribution of the precursor nickel-cobalt-aluminum composite hydroxide, it is preferable that [(d90-d10) / average particle size] is 0.55 or less, and since the proportion of fine particles and large-diameter particles is reduced when the precursor is used as a positive electrode active material, a lithium-ion secondary battery using this positive electrode active material in the positive electrode is safer and can achieve good cycle characteristics and battery output.
[0054] In the index showing the spread of particle size distribution [(d90-d10) / average particle size], d10 means the particle size at which the cumulative volume of the number of particles at each particle size, when accumulated from the smallest particle size, is 10% of the total volume of all particles. In contrast, d90 means the particle size at which the cumulative volume of the number of particles at each particle size, when accumulated from the smallest particle size, is 90% of the total volume of all particles. There are no particular limitations on the method for determining the average particle size, d90, and d10, but they can be determined, for example, from the volume-based distribution measured using a laser diffraction / scattering method.
[0055] [Specific surface area] Nickel-cobalt-aluminum composite hydroxide has a specific surface area of 15 to 60 m 2 It is preferable that the specific surface area is adjusted to 15 to 60 m 2 / g range, when mixed with a lithium compound and fired, a more sufficient particle surface area can be obtained that can come into contact with the molten lithium compound.
[0056] On the other hand, the specific surface area is 15m 2 If the specific surface area is less than 60 m / g, the contact with the molten lithium compound becomes insufficient when mixed with the lithium compound and sintered, and the crystallinity of the resulting lithium nickel cobalt aluminum composite oxide decreases, and when used as a positive electrode material to form a lithium ion secondary battery, lithium diffusion in the solid phase is hindered, which may result in a decrease in capacity. 2 If the specific surface area exceeds 30 to 50 m / g, when the lithium compound is mixed and fired, the crystal growth proceeds too much, and cation mixing occurs in which nickel is mixed into the lithium layer of the lithium transition metal composite oxide, which is a layered compound, and the charge / discharge capacity may decrease, which is not preferable. 2 It is more preferable that the amount of the ionic liquid is adjusted so that the amount of the ionic liquid is / g.
[0057] In particular, nickel-cobalt-aluminum composite hydroxides containing aluminum differ from those not containing aluminum in terms of the unevenness of the particle surface, as well as the size and degree of aggregation of the primary particles. Therefore, the specific surface area of the nickel-cobalt-aluminum composite hydroxide according to one embodiment of the present invention is 30 to 50 m as described above. 2 It is preferable that the ratio is set to / g.
[0058] The method for measuring the specific surface area is not particularly limited, but it can be determined, for example, by the BET multipoint method, the BET single point method, or the nitrogen gas adsorption-desorption method.
[0059] A cross-sectional SEM photograph of the nickel-cobalt-aluminum composite hydroxide according to one embodiment of the present invention is shown in Fig. 1. As shown in Fig. 1, the nickel-cobalt-aluminum composite hydroxide according to one embodiment of the present invention has a solid internal structure.
[0060] According to the nickel-cobalt aluminum composite hydroxide according to one embodiment of the present invention, it is possible to provide a nickel-cobalt aluminum composite hydroxide containing nickel, cobalt, and aluminum, which is a precursor of a positive electrode active material for a lithium-ion secondary battery that can reliably reduce the sodium content and achieve a high capacity.
[0061] <2. Lithium nickel cobalt aluminum composite oxide> A lithium nickel cobalt aluminum composite oxide according to one embodiment of the present invention is composed of secondary particles formed by agglomeration of primary particles containing lithium, nickel, cobalt, and aluminum, or the primary particles and the secondary particles, and is characterized in that the sodium content in the lithium nickel cobalt aluminum composite oxide is less than 0.0005% by mass.
[0062] The lithium nickel cobalt aluminum composite oxide preferably has a sulfate content of 0.15 mass % or less, a chlorine content of 0.005 mass % or less, and a Li site occupancy of 99.0% or more.
[0063] Here, lithium may be washed out of the lithium nickel cobalt aluminum composite oxide by the water washing treatment described later, although the amount may be small. In addition, the more impurities there are in the lithium nickel cobalt aluminum composite oxide, the more adverse effects there are during the firing reaction with the lithium raw material, the worse the crystallinity is, and the more likely lithium is lost during the water washing treatment. Therefore, the lithium nickel cobalt aluminum composite oxide containing aluminum shows a site occupancy rate of Li. Therefore, the Li site occupancy rate of the lithium nickel cobalt aluminum composite oxide according to one embodiment of the present invention is preferably 99.0% or more. In this way, the battery characteristics are further improved.
[0064] The nickel-cobalt-aluminum composite hydroxide can be mixed with a lithium compound and fired to produce a lithium-nickel-cobalt-aluminum composite oxide, which can be used as a raw material for a positive electrode active material for a lithium-ion secondary battery.
[0065] The lithium nickel cobalt aluminum composite oxide used as the positive electrode active material is obtained by mixing the precursor nickel cobalt aluminum composite hydroxide with lithium compounds such as lithium carbonate (Li2CO3: melting point 723°C), lithium hydroxide (LiOH: melting point 462°C), lithium nitrate (LiNO3: melting point 261°C), lithium chloride (LiCl: melting point 613°C), and lithium sulfate (Li2SO4: melting point 859°C), followed by a firing process.
[0066] Regarding the lithium compound, in consideration of ease of handling and stability of quality, it is particularly preferable to use lithium carbonate or lithium hydroxide.
[0067] In this firing process, the carbonate, hydroxyl, nitrate, chlorine, and sulfate radicals, which are also components of the lithium compound, volatilize, but a small portion remains in the positive electrode active material. As for the other non-volatile components such as sodium, the particle size distribution, and the specific surface area, the characteristics of the nickel-cobalt-aluminum composite hydroxide, which is the precursor, are almost the same as those of the positive electrode active material.
[0068] After the firing step, the lithium nickel cobalt aluminum composite oxide containing aluminum is washed with water.
[0069] According to the lithium nickel cobalt aluminum composite oxide according to one embodiment of the present invention, it is possible to provide a positive electrode active material for a lithium ion secondary battery that can reliably reduce the sodium content and achieve a high capacity.
[0070] <3. Manufacturing method of nickel-cobalt-aluminum composite hydroxide> Next, a method for producing a nickel-cobalt aluminum composite hydroxide according to one embodiment of the present invention will be described with reference to Fig. 2. The method for producing a nickel-cobalt aluminum composite hydroxide according to one embodiment of the present invention is a method for producing a precursor of a positive electrode active material, which is composed of secondary particles formed by agglomeration of primary particles containing nickel, cobalt, and aluminum, or the primary particles and the secondary particles. As shown in Fig. 2, the method includes a crystallization step S10 and a washing step S20.
[0071] In the crystallization step S10, a raw material solution containing nickel, cobalt, and aluminum, a solution containing an ammonium ion donor, and an alkaline solution are added to obtain a reaction solution, and crystallization is performed to obtain a transition metal composite hydroxide. Then, in the washing step S20, the transition metal composite hydroxide obtained in the crystallization step S10 is washed with a washing solution.
[0072] The alkaline solution in the crystallization step S10 is a mixed solution of an alkali metal hydroxide and a carbonate, and the molar ratio of the carbonate to the alkali metal hydroxide in the mixed solution is [CO 2- ] / [OH - is 0.002 to 0.050, the crystallization step S10 is performed in a non-oxidizing atmosphere, and the washing solution in the washing step S20 is an ammonium bicarbonate solution having a concentration of 0.05 mol / L or more. Each step will be described in detail below.
[0073] <3-1.Crystallization process> In the crystallization step S10, a raw material solution containing nickel, cobalt, and aluminum, a solution containing an ammonium ion donor, and an alkaline solution are added to obtain a reaction solution, and crystallization is carried out in the reaction solution to obtain a transition metal composite hydroxide.
[0074] It is preferable that the crystallization step S10 further includes a nucleation step S11 and a particle growth step S12. In the nucleation step S11, an alkaline solution is added to generate nuclei in the reaction solution so that the pH measured at a liquid temperature of 25° C. is 12.0 to 14.0, and in the particle growth step S12, it is preferable to add an alkaline solution to the reaction solution containing the nuclei formed in the nucleation step S11 so that the pH measured at a liquid temperature of 25° C. is 10.5 to 12.0. Details will be described later.
[0075] In the conventional continuous crystallization method, the nucleation reaction and the nucleus growth reaction proceed simultaneously in the same reaction tank, resulting in a wide range of particle size distribution of the obtained precursor. In contrast, the method for producing nickel-cobalt-aluminum composite hydroxide in the present invention clearly separates the time when the nucleation reaction mainly occurs (nucleation step) from the time when the particle growth reaction mainly occurs (particle growth step), thereby obtaining a transition metal composite hydroxide with a narrow particle size distribution even if both steps are performed in the same reaction tank. In addition, by using a mixed solution of an alkali metal hydroxide and a carbonate as the alkaline solution, it is possible to reduce impurities such as sulfate radicals.
[0076] The materials and conditions used in the method for producing the nickel-cobalt-aluminum composite hydroxide of the present invention will be described in detail below.
[0077] [Raw material solution containing nickel, cobalt, and aluminum] Metal salts such as nickel salts and cobalt salts used in the raw material solution containing nickel, cobalt, and aluminum are not particularly limited as long as they are water-soluble compounds, and examples of such salts include sulfates, nitrates, chlorides, etc. For example, nickel sulfate and cobalt sulfate are preferably used.
[0078] The concentration of the raw material solution is preferably 1.0 to 2.6 mol / L, more preferably 1.0 to 2.2 mol / L, in terms of the total metal salts. If the concentration is less than 1.0 mol / L, the resulting hydroxide slurry will have a low concentration and will be less productive. On the other hand, if the concentration exceeds 2.6 mol / L, crystal precipitation or freezing will occur at temperatures below -5°C, which may clog the piping of the equipment, and the piping will need to be kept warm or heated, which will be costly.
[0079] Furthermore, the amount of the raw material solution supplied to the reaction tank is preferably such that the crystallization concentration at the time of completion of the crystallization reaction is approximately 30 to 250 g / L, preferably 80 to 150 g / L. If the crystallization concentration is less than 30 g / L, the aggregation of primary particles may be insufficient, and if it exceeds 250 g / L, the diffusion of the added mixed aqueous solution in the reaction tank may be insufficient, resulting in uneven particle growth.
[0080] [Aluminum supplier] It is preferable to use a solution containing sodium aluminate and sodium hydroxide as an aluminum supplier in the crystallization step. When other compounds, such as aluminum sulfate, are used, aluminum hydroxide precipitates at a lower pH than nickel hydroxide or cobalt hydroxide, so aluminum hydroxide is likely to precipitate alone, and it is not possible to obtain a nickel-cobalt-aluminum composite hydroxide with a narrow particle size distribution and uniform particle size.
[0081] The aluminum donor can be obtained, for example, by dissolving a predetermined amount of sodium aluminate in water to prepare an aqueous solution, and adding a predetermined amount of sodium hydroxide. At this time, the molar ratio of sodium to aluminum in the aluminum donor is more preferably 1.0 to 3.0. If the amount of sodium, i.e., the amount of sodium hydroxide, is out of the range of 1.0 to 3.0 in terms of molar ratio, the stability of the aluminum donor decreases, and aluminum hydroxide is likely to precipitate as fine particles immediately after or before it is added to the reaction tank. As a result, the coprecipitation reaction with nickel hydroxide and cobalt hydroxide becomes difficult to occur, and a nickel-cobalt-aluminum composite hydroxide with a wide particle size distribution and varying particle size is generated, and there is a possibility that problems such as uneven dispersion of aluminum particles may occur, which is not preferable.
[0082] In order to uniformly disperse aluminum in the nickel-cobalt-aluminum composite hydroxide, a raw material solution containing nickel and cobalt and an aluminum supplier are added to a reaction tank at the same time. At this time, the metal concentrations of nickel, cobalt, and aluminum and the addition flow rates of the raw material solution and the aluminum supplier are adjusted so that the nickel-cobalt-aluminum composite hydroxide has a target composition ratio.
[0083] [Ammonium ion donor] The ammonium ion donor in the reaction solution is not particularly limited as long as it is a water-soluble compound, and examples of the donor include ammonia water, ammonium sulfate, ammonium chloride, ammonium carbonate, and ammonium fluoride. For example, it is preferable to use ammonia water or ammonium sulfate.
[0084] The ammonium ion concentration in the reaction solution is adjusted to be preferably 3 to 25 g / L, more preferably 10 to 20 g / L, and even more preferably 5 to 15 g / L. The presence of ammonium ions in the reaction solution causes metal ions, particularly nickel ions, to form ammine complexes, which increases the solubility of metal ions and promotes the growth of primary particles, making it easy to obtain dense nickel-cobalt-aluminum composite hydroxide particles. Furthermore, since the solubility of metal ions is stable, nickel-cobalt-aluminum composite hydroxide particles with a uniform shape and particle size are easily obtained. And, by setting the ammonium ion concentration in the reaction solution to 3 to 25 g / L, it is easy to obtain composite hydroxide particles that are denser and have a uniform shape and particle size.
[0085] If the ammonium ion concentration in the reaction solution is less than 3 g / L, the solubility of the metal ions may become unstable, and primary particles with uniform shape and particle size may not be formed, and gel-like nuclei may be generated, resulting in a wide particle size distribution. On the other hand, if the ammonium ion concentration exceeds 25 g / L, the solubility of the metal ions may become too high, and the amount of metal ions remaining in the reaction solution may increase, causing a deviation in the composition. The concentration of ammonium ions can be measured using an ion electrode method (ion meter).
[0086] [Alkaline solution] The alkaline solution is prepared by mixing alkali metal hydroxide and carbonate. The molar ratio of the alkali metal hydroxide to the carbonate is [CO3 2- ] / [OH - ] is from 0.002 to 0.050, more preferably from 0.005 to 0.030, and further preferably from 0.010 to 0.025.
[0087] By using a mixed solution of an alkali metal hydroxide and a carbonate as the alkaline solution, it is possible to replace and remove anions such as sulfate radicals and chlorine radicals remaining as impurities in the nickel-cobalt-aluminum composite hydroxide obtained in the crystallization process with carbonate radicals. Carbonate radicals are more easily volatilized by ignition than sulfate radicals and chlorine radicals, and are preferentially volatilized in the process of mixing the nickel-cobalt-aluminum composite hydroxide with a lithium compound and baking it, so that almost no carbonate radicals remain in the lithium-nickel-cobalt-aluminum composite oxide, which is the positive electrode material.
[0088] [CO3 2- ] / [OH - If the [CO3 2- ] / [OH - Even if the ratio exceeds 0.050, the reduction in impurities such as sulfate and chlorine derived from the raw materials remains unchanged, and the addition of an excess of carbonate increases costs.
[0089] The alkali metal hydroxide is preferably one or more of lithium hydroxide, sodium hydroxide, and potassium hydroxide, and a compound that is easily soluble in water is preferable because the amount added can be easily controlled.
[0090] The carbonate is preferably one or more of sodium carbonate, potassium carbonate, and ammonium carbonate, and a compound that is easily soluble in water is preferred because the amount added can be easily controlled.
[0091] The method for adding the alkaline solution to the reaction tank is not particularly limited, and the alkaline solution may be added using a pump capable of controlling the flow rate, such as a metering pump, so that the pH of the reaction solution is maintained within the range described below.
[0092] [pH control] It is more preferable that the crystallization step S10 comprises a nucleation step S11 in which an alkaline solution is added to generate nuclei so that the pH of the reaction solution, measured at a liquid temperature of 25°C, is 12.0 to 14.0, and a particle growth step S12 in which an alkaline solution is added to a particle growth solution containing the nuclei formed in the nucleation step S11 so that the pH of the solution, measured at a liquid temperature of 25°C, is 10.5 to 12.0, to grow the nuclei.
[0093] In other words, the nucleation reaction and the particle growth reaction do not proceed at the same time in the same tank, but the time during which the nucleation reaction (nucleation step S11) mainly occurs and the time during which the particle growth reaction (particle growth step S12) mainly occurs are clearly separated. The nucleation step S11 and the particle growth step S12 will be described in detail below.
[0094] <3-1-1. Nucleation process> In the nucleation step S11, it is preferable to control the pH of the reaction solution to be in the range of 12.0 to 14.0 at a liquid temperature of 25° C. If the pH exceeds 14.0, the nuclei formed may become too fine, causing the reaction solution to gel. If the pH is less than 12.0, the nuclei may grow together with the nuclei formed, causing the particle size distribution of the nuclei to be broadened, resulting in inhomogeneous nuclei.
[0095] That is, in the nucleation step S11, by controlling the pH of the reaction solution in the range of 12.0 to 14.0, it is possible to suppress the growth of nuclei and cause only nucleation to occur, and the nuclei formed can be made homogeneous and have a narrower particle size distribution range.
[0096] <3-1-2. Particle growth process> In the particle growth step S12, the pH of the reaction solution is preferably 10.5 to 12.0, more preferably 11.0 to 12.0, based on a liquid temperature of 25° C. If the pH exceeds 12.0, the number of newly generated nuclei increases, resulting in the generation of fine secondary particles, and it may not be possible to obtain a hydroxide with a good particle size distribution. If the pH is less than 10.5, the solubility of ammonium ions is high, and the amount of metal ions remaining in the liquid without precipitating increases, which may result in a decrease in production efficiency.
[0097] That is, by controlling the pH of the reaction solution in the particle growth step S12 within the range of 10.5 to 12.0, it is possible to preferentially cause the growth of only the nuclei generated in the nucleation step S11 and suppress the formation of new nuclei, and it is possible to obtain a nickel-cobalt-aluminum composite hydroxide that is homogeneous and has a narrower particle size distribution range.
[0098] In addition, since a pH of 12.0 is a boundary condition between nucleation and nucleus growth, the conditions can be set to either the nucleation step or the particle growth step depending on the presence or absence of nuclei in the reaction solution. That is, if the pH in the nucleation step S11 is made higher than 12.0 to generate a large amount of nuclei, and then the pH is made 12.0 in the particle growth step S12, the large amount of nuclei is present in the reaction aqueous solution, so that the growth of the nuclei takes precedence, and the above hydroxide having a narrower particle size distribution and a relatively large particle size is obtained.
[0099] On the other hand, when no nuclei are present in the reaction solution, that is, when the pH is set to 12.0 in the nucleation step S11, there are no nuclei to grow, and nucleation takes precedence. By setting the pH in the particle growth step S12 to a value lower than 12.0, the generated nuclei grow, resulting in a better hydroxide.
[0100] In either case, the pH of the particle growth step S12 may be controlled to a value lower than the pH of the nucleation step S11. In order to clearly separate nucleation and particle growth, the pH of the particle growth step S12 is preferably 0.5 or more lower than the pH of the nucleation step S11, and more preferably 1.0 or more lower.
[0101] As described above, by clearly separating the nucleation step S11 and the particle growth step S12 by pH, nucleation occurs preferentially in the nucleation step S11, with little nucleus growth, and conversely, only nucleus growth occurs in the particle growth step S12, with almost no new nuclei being generated. As a result, in the nucleation step S11, homogeneous nuclei with a narrow particle size distribution range can be formed, and in the particle growth step S12, the nuclei can be grown homogeneously. Therefore, in the method for producing nickel-cobalt-aluminum composite hydroxide, homogeneous nickel-cobalt-aluminum composite hydroxide particles with a narrower particle size distribution range can be obtained.
[0102] [Reaction solution temperature] In the reaction tank, the temperature of the reaction solution is preferably set to 20 to 80°C, more preferably 30 to 70°C, and even more preferably 35 to 60°C. When the temperature of the reaction solution is less than 20°C, the solubility of metal ions is low, so that nucleation is likely to occur and control becomes difficult. On the other hand, when the temperature exceeds 80°C, the volatilization of ammonia is promoted, so that an excess of ammonium ion donor must be added to maintain a predetermined ammonia concentration, which increases costs.
[0103] [Reaction atmosphere] The particle size and particle structure of the nickel-cobalt-aluminum composite hydroxide are also controlled by the reaction atmosphere in the crystallization step S10. Therefore, in the crystallization step S10, crystallization is performed in a non-oxidizing atmosphere. When the atmosphere in the reaction tank in the crystallization step S10 is controlled to be a non-oxidizing atmosphere, the growth of the primary particles forming the nickel-cobalt-aluminum composite hydroxide is promoted, and the primary particles are large and dense, and secondary particles having a moderately large particle size are formed. In particular, by setting the non-oxidizing atmosphere in the crystallization step S10 with an oxygen concentration of 5.0 volume % or less, preferably 2.5 volume % or less, and more preferably 1.0 volume % or less, nuclei are generated from relatively large primary particles, and particle growth is promoted by the aggregation of the primary particles, so that secondary particles of a moderate size can be obtained. Therefore, a solid-type nickel-cobalt-aluminum composite hydroxide as shown in FIG. 1 is obtained. On the other hand, when the atmosphere in the reaction tank during the crystallization step is controlled to be an oxidizing atmosphere, the growth of the primary particles that form the nickel-cobalt-aluminum composite hydroxide is suppressed, and secondary particles that are made of fine primary particles and have a large number of spaces or fine voids dispersed in the center of the particles are formed.
[0104] The non-oxidizing atmosphere refers to a mixed atmosphere of oxygen with an oxygen concentration of 5.0% by volume or less, preferably 2.5% by volume or less, more preferably 1.0% by volume or less, and an inert gas. As a means for maintaining the space in the reaction tank in such a non-oxidizing atmosphere, an inert gas such as nitrogen can be circulated through the space in the reaction tank, and further, an inert gas can be bubbled into the reaction solution. In the crystallization step S10, the preferred flow rate of the bubbling is 3 to 7 L / min, more preferably about 5 L / min.
[0105] On the other hand, an oxidizing atmosphere refers to an atmosphere in which the oxygen concentration exceeds 5.0% by volume, preferably 10.0% by volume or more, and more preferably 15.0% by volume or more.
[0106] When creating a solid structure such as the nickel-cobalt-aluminum composite hydroxide according to one embodiment of the present invention, it is preferable to make the atmosphere in the reaction tank an inert atmosphere or a non-oxidizing atmosphere in which the oxygen concentration is controlled to 0.2% by volume or less during the crystallization step S10.
[0107] The nucleation step S11 and the particle growth step S12 have been described above, but while the nucleation and particle growth are being carried out, the reaction atmosphere is controlled in parallel.
[0108] <2-2. Cleaning process> In the washing step S20, the transition metal composite hydroxide obtained in the crystallization step S10 is washed with a washing liquid.
[0109] [Cleaning solution type] In the washing step S20, washing is performed with a washing solution based on an alkali metal salt or ammonium salt of carbonate, hydrogen carbonate (bicarbonate), or hydroxide. Preferably, the transition metal composite hydroxide is washed with a washing solution in which carbonate, hydrogen carbonate (bicarbonate), or a mixture thereof is dissolved in water.
[0110] In this way, it is possible to efficiently remove anions such as sulfate radicals and chlorine radicals, which are impurities, by utilizing a substitution reaction with carbonate ions and hydrogen carbonate ions (bicarbonate ions) in the cleaning solution. In addition, by using carbonates and hydrogen carbonates (bicarbonates), it is possible to suppress the inclusion of alkali metals such as sodium, compared to when hydroxides are used. In addition, when hydroxides are used in transition metal composite hydroxides having a porous structure, it is difficult to remove impurities inside the particles, and in this respect, too, it is more effective to use carbonates and hydrogen carbonates (bicarbonates).
[0111] As the carbonate, it is preferable to select sodium carbonate, potassium carbonate, or ammonium carbonate, and as the hydrogen carbonate (bicarbonate), it is preferable to select sodium hydrogen carbonate, potassium hydrogen carbonate, or ammonium hydrogen carbonate. Furthermore, by selecting an ammonium salt from among the carbonates and hydrogen carbonates (bicarbonates), it is possible to efficiently remove cations such as sodium, which are impurities, by utilizing a substitution reaction with the ammonium ions in the cleaning solution. Furthermore, by selecting ammonium hydrogen carbonate from among the ammonium salts, it is possible to most efficiently remove cations such as sodium.
[0112] This is because it is believed that not only the replacement reaction between cations such as sodium and ammonium ions, but also the superior properties of ammonium bicarbonate compared to other salts, namely, the high foaming efficiency of carbon dioxide gas when used as a cleaning solution, greatly contribute to the removal of cations such as sodium.
[0113] [Concentration and pH] The concentration of the ammonium bicarbonate solution used as the cleaning solution must be 0.05 mol / L or more. If the concentration is less than 0.05 mol / L, the effect of removing impurities such as sulfate, chlorine, and sodium may decrease. If the concentration is 0.05 mol / L or more, the effect of removing these impurities will not change. Therefore, adding too much ammonium bicarbonate (ammonium bicarbonate) will increase costs and affect the environmental load such as wastewater standards, so it is preferable to set the upper limit concentration at around 1.0 mol / L.
[0114] In addition, if the concentration of the ammonium bicarbonate solution is 0.05 mol / L or more, there is no need to adjust the pH, and the pH can be left as it is. If the concentration is 0.05 to 1.0 mol / L, the pH will be in the range of approximately 8.0 to 9.0.
[0115] [Liquid temperature] The temperature of the ammonium bicarbonate solution serving as the cleaning liquid is not particularly limited, but is preferably 15 to 50° C. If the liquid temperature is within the above range, the substitution reaction with impurities and the bubbling effect of carbon dioxide gas generated from ammonium bicarbonate are more favorable, and the removal of impurities proceeds efficiently.
[0116] [Liquid volume] The amount of the ammonium hydrogen carbonate solution, which is the cleaning solution, is preferably 1 to 20 L per 1 kg of nickel-cobalt-aluminum composite hydroxide (slurry concentration is 50 to 1000 g / L). If the amount is less than 1 L, the impurity removal effect may not be sufficient. Even if a liquid amount exceeding 20 L is used, the impurity removal effect remains the same, and an excessive liquid amount increases costs, affects environmental loads such as wastewater standards, and is also a factor in increasing the load of wastewater in wastewater treatment.
[0117] [Washing time] The washing time with the ammonium hydrogen carbonate solution is not particularly limited as long as it can sufficiently remove impurities, but is usually 0.5 to 2 hours.
[0118] [Cleaning method] The washing method may be 1) a general washing method in which nickel-cobalt-aluminum composite hydroxide is added to an ammonium hydrogen carbonate solution, the slurry is stirred and washed, and then filtered, or 2) a liquid-passing washing method may be performed in which a slurry containing nickel-cobalt-aluminum composite hydroxide produced by neutralization crystallization is supplied to a filter such as a filter press and an ammonium hydrogen carbonate solution is passed through the slurry. Liquid-passing washing is more preferable because it has a high impurity removal effect, filtration and washing can be performed continuously in the same equipment, and productivity is high.
[0119] After washing with the ammonium hydrogen carbonate solution, the washing liquid containing the impurities washed out by the substitution reaction may adhere to the nickel-cobalt-aluminum composite hydroxide, so it is preferable to finally wash with water. Furthermore, after washing with water, it is preferable to perform a drying step (not shown) in which the adhering water on the filtered nickel-cobalt-aluminum composite hydroxide is dried.
[0120] The nickel-cobalt aluminum composite hydroxide obtained through the washing step S20 is a precursor of a positive electrode active material composed of secondary particles in which primary particles containing nickel, cobalt, and aluminum are aggregated, or the primary particles and the secondary particles, and is characterized in that the sodium content in the nickel-cobalt aluminum composite hydroxide is less than 0.0005 mass %.
[0121] According to the method for producing a nickel-cobalt aluminum composite hydroxide according to one embodiment of the present invention, it is possible to provide a method for producing a nickel-cobalt aluminum composite hydroxide containing nickel, cobalt, and aluminum, which is a precursor of a positive electrode active material for a lithium-ion secondary battery that reliably reduces the sodium content, and enables a high capacity to be achieved. EXAMPLES
[0122] Next, the nickel-cobalt-aluminum composite hydroxide, the method for producing the nickel-cobalt-aluminum composite hydroxide, and the lithium-nickel-cobalt-aluminum composite oxide according to one embodiment of the present invention will be described in detail with reference to examples. Note that the present invention is not limited to these examples.
[0123] For Examples 1 to 16 and Comparative Examples 1 to 8, the transition metal composite hydroxide obtained in the crystallization step was washed, filtered, and dried to recover the precursor nickel-cobalt-aluminum composite hydroxide, and then various analyses were carried out by the following methods.
[0124] [composition] The composition was analyzed by acid decomposition-ICP emission spectrometry, and a multi-type ICP emission spectrometry analyzer, ICPE-9000 (manufactured by Shimadzu Corporation), was used for the measurements.
[0125] [Sodium content] The sodium content was analyzed by acid decomposition-atomic absorption spectrometry, and the measurement was performed using an atomic absorption spectrophotometer 240AA (Agilent Technologies, Inc.), an atomic absorption analyzer.
[0126] [Sulfate root content] The sulfate radical content was determined by analyzing the total sulfur content using acid decomposition-ICP emission spectrometry, and the total sulfur content was calculated by dividing the total sulfur content by the sulfate radical (SO4 2- The measurement was performed using a multi-type ICP emission spectrometer, ICPE-9000 (Shimadzu Corporation).
[0127] [Chlorine content] The chlorine radical content was analyzed by X-ray fluorescence spectrometry (XRF) either directly from the sample or by separating the chlorine radical contained in the sample in the form of silver chloride by distillation. The measurement was performed using an X-ray fluorescence analyzer, Axios (manufactured by Spectris Corporation).
[0128] [Average particle size and particle size distribution] The mean particle size (MV) and particle size distribution [(d90-d10) / mean particle size] were determined from the volume distribution measured using a laser diffraction / scattering method, using a Microtrac MT3300EXII (Microtrac Bell Co., Ltd.), a particle size distribution measuring device using the laser diffraction / scattering method.
[0129] [Specific surface area] The specific surface area was analyzed by the nitrogen gas adsorption-desorption method using the BET single point method, and a gas flow type specific surface area measuring device, the Maxsorb 1200 series (manufactured by Mountec Co., Ltd.), was used for the measurement.
[0130] [Production and evaluation of positive electrode active material] Furthermore, the lithium metal composite oxide, more specifically the lithium nickel cobalt aluminum composite oxide, which is the positive electrode active material made from the nickel cobalt aluminum composite hydroxide of the present invention, was produced and evaluated by the following method.
[0131] [A. Production of positive electrode active material] The precursor nickel-cobalt-aluminum composite hydroxide was heat-treated in an air stream (oxygen: 21% by volume) at 700°C for 6 hours to recover the metal composite oxide. In addition, lithium hydroxide, a lithium compound, was weighed out so that Li / Me=1.025, and mixed with the recovered metal composite oxide to produce a lithium mixture. A shaker mixer (Willi & Bachofen (WAB) TURBULA-Type T2C) was used for the mixing operation.
[0132] Next, the prepared lithium mixture was calcined at 500°C for 4 hours in an oxygen stream (oxygen: 100% by volume), further sintered at 730°C for 24 hours, cooled and then crushed to obtain a lithium nickel cobalt aluminum composite oxide.
[0133] [B. Evaluation of positive electrode active material] The above-mentioned analytical method and analytical equipment were used to analyze the sodium content, sulfate content, and chlorine content of the obtained lithium nickel cobalt aluminum composite oxide. The Li site occupancy rate, which indicates the crystallinity of the lithium nickel cobalt aluminum composite oxide, was calculated by Rietveld analysis from the diffraction pattern measured using an X-ray diffraction analyzer (XRD). The X-ray diffraction analyzer X'Pert-PRO (manufactured by Spectris Co., Ltd.) was used for the measurement. The Li site occupancy rate indicates the proportion of lithium element in the lithium layer (Li site) of the layered structure of the lithium nickel cobalt aluminum composite oxide. The Li site occupancy rate is correlated with the battery characteristics, and the higher the Li site occupancy rate, the better the battery characteristics.
[0134] The conditions for the examples and comparative examples will be described below.
[0135] Example 1 In Example 1, 0.9 L of water was placed in a crystallization reaction tank (5 L) in the crystallization step, and the temperature inside the tank was set to 50° C. while stirring. Nitrogen gas was circulated through the reaction tank to create a nitrogen atmosphere. The oxygen concentration in the reaction tank space at this time was 2.0% by volume.
[0136] An appropriate amount of 25% sodium hydroxide aqueous solution and 25% ammonia water, which is an ammonium ion donor, were added to the water in the reaction tank, and the pH of the reaction solution in the tank was adjusted to 12.8, measured based on a liquid temperature of 25° C. The ammonium ion concentration of the reaction solution was also adjusted to 10 g / L.
[0137] Next, nickel sulfate and cobalt chloride were dissolved in water to prepare a 2.0 mol / L raw material solution. In this raw material solution, the elemental molar ratio of each metal was adjusted to Ni:Co = 0.84:0.16. Separately, a predetermined amount of sodium aluminate was dissolved in water, and 25% sodium hydroxide solution was added to the solution so that the molar ratio of sodium to aluminum was 1.7 to prepare an aluminum supplier. Furthermore, sodium hydroxide, which is an alkali metal hydroxide, and sodium carbonate, which is a carbonate, were dissolved in [CO3 2- ] / [OH - An alkaline solution was prepared by dissolving it in water so that the value of [C] was 0.025.
[0138] The raw material solution was added to the reaction solution in the reaction tank at 12.9 ml / min, and the ammonium ion donor and alkaline solution were also added to the reaction solution at a constant rate, and while the ammonium ion concentration in the reaction solution was maintained at 10 g / L, the pH was controlled to 12.8 (nucleation step pH), and crystallization was carried out for 2 minutes and 30 seconds to perform nucleation. The addition rate of the aluminum donor was adjusted so that the metal element molar ratio of the slurry was Ni:Co:Al = 81:16:3.
[0139] Thereafter, 64% sulfuric acid was added until the pH of the reaction solution reached 11.6 (particle growth step pH) as measured at a liquid temperature of 25° C. After the pH of the reaction solution reached 11.6 as measured at a liquid temperature of 25° C., the supply of the raw material solution, aluminum donor, ammonium ion donor, and alkaline solution was resumed, and the pH was controlled at 11.6 while crystallization was continued for 4 hours to grow particles, thereby obtaining a transition metal composite hydroxide.
[0140] The obtained transition metal composite hydroxide was subjected to solid-liquid separation using a filter press filter, and then impurities were removed by passing 5 L of the washing solution through the filter press filter per 1 kg of the transition metal composite hydroxide using a 0.05 mol / L ammonium bicarbonate solution as a washing solution, and then water was passed through the filter press filter for washing. Then, the water adhering to the washed transition metal composite hydroxide was dried to obtain a nickel-cobalt-aluminum composite hydroxide as a precursor.
[0141] Example 2 In Example 2, a nickel-cobalt-aluminum composite hydroxide was obtained in the same manner as in Example 1, except that the addition rate of the aluminum supplier was adjusted so that the molar ratio of metal elements in the slurry was Ni:Co:Al=78:15:7.
[0142] Example 3 In Example 3, a nickel-cobalt-aluminum composite hydroxide was obtained in the same manner as in Example 1, except that the addition rate of the aluminum supplier was adjusted so that the molar ratio of metal elements in the slurry was Ni:Co:Al=74:14:12.
[0143] Example 4 In Example 4, a nickel-cobalt-aluminum composite hydroxide was obtained in the same manner as in Example 1, except that the addition rate of the aluminum supplier was adjusted so that the molar ratio of metal elements in the slurry was Ni:Co:Al=69:13:18.
[0144] Example 5 In Example 5, when preparing the alkaline solution, [CO3 2- ] / [OH - A nickel-cobalt-aluminum composite hydroxide was obtained in the same manner as in Example 1, except that the value of [Ratio of Hydrogen Peroxide to Hydrogen Peroxide] was adjusted to 0.003.
[0145] Example 6 In Example 6, when preparing the alkaline solution, [CO3 2- ] / [OH -A nickel-cobalt-aluminum composite hydroxide was obtained in the same manner as in Example 1, except that the value of [(a)-(b)] was adjusted to 0.048.
[0146] Example 7 In Example 7, a nickel-cobalt-aluminum composite hydroxide was obtained in the same manner as in Example 1, except that in preparing the aluminum donor, a 25% sodium hydroxide solution was added to a solution in which sodium aluminate was dissolved in water so that the ratio of sodium to aluminum became 1.0.
[0147] Example 8 In Example 8, in preparing the aluminum donor, a nickel-cobalt-aluminum composite hydroxide was obtained in the same manner as in Example 1, except that a 25% aqueous solution of sodium hydroxide was added to a solution in which sodium aluminate was dissolved in water so that the ratio of sodium to aluminum was 3.0.
[0148] Example 9 In Example 9, a nickel-cobalt-aluminum composite hydroxide was obtained in the same manner as in Example 1, except that the pH in the nucleation step was 13.6.
[0149] Example 10 In Example 10, a nickel-cobalt-aluminum composite hydroxide was obtained in the same manner as in Example 1, except that the pH in the nucleation step was 12.3.
[0150] Example 11 In Example 11, a nickel-cobalt-aluminum composite hydroxide was obtained in the same manner as in Example 1, except that the pH in the particle growth step was 11.8.
[0151] Example 12 In Example 12, a nickel-cobalt-aluminum composite hydroxide was obtained in the same manner as in Example 1, except that the pH in the particle growth step was 10.6.
[0152] (Example 13) In Example 13, a nickel-cobalt-aluminum composite hydroxide was obtained in the same manner as in Example 1, except that when preparing the alkaline solution, potassium hydroxide was used as the alkali metal hydroxide and potassium carbonate was used as the carbonate.
[0153] Example 14 In Example 14, a nickel-cobalt-aluminum composite hydroxide was obtained in the same manner as in Example 1, except that, when preparing the alkaline solution, ammonium carbonate was used as the carbonate and the ammonium ion concentration was adjusted to 20 g / L.
[0154] Example 15 In Example 15, a nickel-cobalt-aluminum composite hydroxide was obtained in the same manner as in Example 1, except that the temperature in the tank was set to 35°C.
[0155] (Example 16) In Example 16, a nickel-cobalt-aluminum composite hydroxide was obtained in the same manner as in Example 1, except that an ammonium hydrogen carbonate solution with a concentration of 1.00 mol / L was used as the cleaning liquid.
[0156] Comparative Example 1 In Comparative Example 1, only sodium hydroxide was used to prepare the alkaline solution, and [CO3 2- ] / [OH - A nickel-cobalt-aluminum composite hydroxide was obtained in the same manner as in Example 1, except that the above-mentioned step (1) was not taken into consideration.
[0157] Comparative Example 2 In Comparative Example 2, when preparing the alkaline solution, [CO3 2- ] / [OH - A nickel-cobalt-aluminum composite hydroxide was obtained in the same manner as in Example 1, except that the value of [Ratio of Hydrogen Peroxide to Hydrogen Peroxide] was adjusted to 0.001.
[0158] Comparative Example 3 In Comparative Example 3, when preparing the alkaline solution, [CO3 2- ] / [OH -A nickel-cobalt-aluminum composite hydroxide was obtained in the same manner as in Example 1, except that the value of [Ratio of Hydrogen Permeability] was adjusted to 0.055.
[0159] Comparative Example 4 In Comparative Example 4, a nickel-cobalt-aluminum composite hydroxide was obtained in the same manner as in Example 1, except that the washing step was omitted and washing with an ammonium hydrogen carbonate solution was not performed.
[0160] Comparative Example 5 In Comparative Example 5, a nickel-cobalt-aluminum composite hydroxide was obtained in the same manner as in Example 1, except that an ammonium hydrogen carbonate solution with a concentration of 0.02 mol / L was used as the cleaning liquid.
[0161] Comparative Example 6 In Comparative Example 6, a nickel-cobalt-aluminum composite hydroxide was obtained in the same manner as in Example 1, except that an ammonium carbonate solution was used as the cleaning liquid.
[0162] Comparative Example 7 In Comparative Example 7, a nickel-cobalt-aluminum composite hydroxide was obtained in the same manner as in Example 1, except that a sodium hydrogen carbonate solution was used as the cleaning liquid.
[0163] Comparative Example 8 In Comparative Example 8, a nickel-cobalt-aluminum composite hydroxide was obtained in the same manner as in Example 1, except that a sodium carbonate solution was used as the washing liquid.
[0164] The above conditions and results are shown in Tables 1 and 2.
[0165] [Table 1]
[0166] [Table 2]
[0167] (comprehensive evaluation) As shown in Tables 1 and 2, in Examples 1 to 16, the conditions of the crystallization step and the washing step in the nickel-cobalt-aluminum composite hydroxide, which is the precursor, were all within the preferred range. Therefore, not only the nickel-cobalt-aluminum composite hydroxide but also the lithium-nickel-cobalt-aluminum composite oxide, which is the positive electrode active material, were sufficiently reduced in the impurity removal, including the sodium content, sulfate content, and chlorine content. Furthermore, in the lithium-nickel-cobalt-aluminum composite oxide, the Li site occupancy rate exceeded 99.0%, resulting in excellent crystallinity and improved battery characteristics.
[0168] In particular, the sodium content of both the precursor and the positive electrode active material was very good, with all of the example data being less than the quantitative (analytical) value (0.0005% by mass).
[0169] Here, the lower limit of quantification means the minimum amount or minimum concentration that can be analyzed (quantified) by a certain analytical method. The minimum amount (value) at which a signal of the target component can be detected in a measurement is called the detection limit, and the minimum amount (value) at which the signal of the target component obtained in a measurement is guaranteed to be reliable is called the measurement limit. Furthermore, the lower limit of quantification can be calculated by multiplying the measurement limit by a dilution factor that indicates how much the original analytical sample has been concentrated or diluted in the process of preparing the analytical sample into a measurement specimen liquid.
[0170] In other words, in the present invention, the sodium content is 0.05 μg / mL, which is the lower limit of measurement by an atomic absorption spectrometer, and since 1 g of the analytical sample was acid-decomposed to prepare 100 mL of measurement specimen liquid (dilution ratio: 100 times), the lower limit of quantification is 5 ppm (μg / g), or 0.0005% by mass.
[0171] In contrast, in Comparative Examples 1 to 8, the amount of [CO3 2- ] / [OH -], the concentration of the cleaning solution, ammonium bicarbonate solution, was not within the preferred range, a cleaning solution other than ammonium bicarbonate solution was used, and other conditions were deviated from the optimal conditions, so that the excellent effects of the examples were not obtained.
[0172] As a result, it has been possible to provide a nickel-cobalt-aluminum composite hydroxide containing nickel, cobalt, and aluminum, which is a precursor of a positive electrode active material for a lithium-ion secondary battery that can reliably reduce the sodium content in particular and increase capacity, a method for producing the nickel-cobalt-aluminum composite hydroxide, and a lithium-nickel-cobalt-aluminum composite oxide. It is also expected that this will lead to the provision of a lithium-ion secondary battery with excellent characteristics.
[0173] Although the embodiments and examples of the present invention have been described in detail above, those skilled in the art will easily understand that many modifications are possible without substantially departing from the novel features and effects of the present invention. Therefore, all such modifications are intended to be included within the scope of the present invention.
[0174] For example, a term described at least once in the specification or drawings together with a different term having a broader or similar meaning can be replaced with the different term anywhere in the specification or drawings. The nickel-cobalt-aluminum composite hydroxide, the method for producing the nickel-cobalt-aluminum composite hydroxide, and the configuration and operation of the lithium-nickel-cobalt-aluminum composite oxide are not limited to those described in the respective embodiments and examples of the present invention, and various modifications are possible. [Explanation of symbols]
[0175] S10 crystallization process, S11 nucleation process, S12 particle growth process, S20 washing process
Claims
1. A nickel-cobalt-aluminum composite hydroxide, which is a precursor of a positive electrode active material, is composed of secondary particles in which primary particles containing nickel, cobalt, and aluminum are aggregated, or the primary particles and the secondary particles, The nickel-cobalt-aluminum composite hydroxide has a sodium content of less than 0.0005% by mass and a chlorine content of 0.01% by mass or less.
2. The specific surface area of the nickel-cobalt-aluminum composite hydroxide is 30 to 50 m 2 The nickel-cobalt-aluminum composite hydroxide according to claim 1, characterized in that the nickel-cobalt-aluminum composite hydroxide has a molecular weight of 1.0 to 1.0 g.
3. 3. The nickel-cobalt-aluminum composite hydroxide according to claim 1, wherein the content of sulfate radicals contained in the nickel-cobalt-aluminum composite hydroxide is 0.2 mass % or less.
4. The nickel-cobalt-aluminum composite hydroxide according to any one of claims 1 to 3, characterized in that [(d90-d10) / average particle size], which is an index indicating the spread of the particle size distribution of the nickel-cobalt-aluminum composite hydroxide, is 0.55 or less. The nickel-cobalt-aluminum composite hydroxide according to any one of claims 1 to 3.
5. The nickel-cobalt-aluminum composite hydroxide has the general formula: Ni 1-x-y Co x A y (OH) 2+a The nickel-cobalt-aluminum composite hydroxide according to any one of claims 1 to 4, characterized in that: (wherein 0.05≦x≦0.35, 0.01≦y≦0.20, x + y <0.40, and 0≦a≦0.5).
Citation Information
Patent Citations
Powder of lithium complex compound particle, method for producing the same, and nonaqueous electrolyte secondary cell
JP2010155775A
Li-Ni COMPLEX OXIDE PARTICLE POWDER, METHOD FOR MANUFACTURING THE SAME, AND NONAQUEOUS ELECTROLYTE SECONDARY BATTERY
JP2012230898A
Positive electrode active material for nonaqueous electrolyte secondary batteries, method for manufacturing the same, and nonaqueous electrolyte secondary battery arranged by use thereof
JP2015122269A
Positive electrode active material precursor for nonaqueous electrolyte secondary batteries and producing method thereof, and positive electrode active material for nonaqueous electrolyte secondary batteries and producing method thereof
JP2015128004A
Precursor of positive electrode active material for nonaqueous electrolyte secondary batteries and manufacturing method thereof, and positive electrode active material for nonaqueous electrolyte secondary batteries and manufacturing method thereof
JP2015191848A